Appetitive responses of purple mud crab (Scylla tranquebarica) towards formulated diet leachates made of various marine protein sources - Lim, Yew Jun; Liew, Kit Shing; Liew, Hon Jung; Annette Jaya‑Ram; Kianann Tan; Yong, Annita Seok Kian; Rossita Shapawi; Uun Yanuhar; Lim, Leong Seng (Springer Nature, 2025)
The present study evaluated the attractability of diets formulated with various marine protein sources to the Scylla tranquebarica by examining their appetitive responses towards the diets’ leachates. Six experimental diets were formulated using fish meal (FM), sergestid shrimp meal (SSM), and squid meal (SQM), which were FM100 (100% FM protein), SSM100, SQM100, FM50SSM50 (50% FM and 50% SSM proteins), FM50SQM50, and SSM50SQM50. These pelleted diets were immersed in seawater, stirred, and filtered to collect their leachates. Additionally, clam extract (CE) and seawater (SW) were used as positive and negative controls, respectively. The appetitive responses of S. tranquebarica were examined and evaluated using a scoring method, with the mean scores (maximum = 3.0) of each leachate and both controls as follows: SW (0.00), FM100 (2.05), FM50SSM50 (2.11), SQM100 (2.26), SSM50SQM50 (2.32), FM50SQM50 (2.37), SSM100 (2.42), and CE (2.68). Among all leachates, only the mean scores of SSM100 and FM50SQM50 were not significantly different (p > 0.05) from that of CE, which demonstrated that both diets were as attractive as the natural food extract. In conclusion, this finding confirms that sergestid shrimp meal and squid meal are highly attractive protein sources, and they are suitable for use in formulated diet for Scylla mud crabs.